2022
DOI: 10.1039/d1cp05713h
|View full text |Cite
|
Sign up to set email alerts
|

Core-electron contributions to the molecular magnetic response

Abstract: Orbital contributions to the magnetic response and molecular magnetic properties depend on the method used to compute them. Here, we show that dissecting nuclear magnetic shielding tensors using natural localized...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
46
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(49 citation statements)
references
References 55 publications
3
46
0
Order By: Relevance
“…Albeit being widely used, the NICS values may be articially lowered by the local paramagnetic current around the Pr nucleus in PrB 2 À , thus may give negative values even if a global ring-current is non-existent and fail to assess aromaticity in some metallic systems. [96][97][98][99][100] However, the NICS values can still help to provide helpful information about aromaticity when combining with other criteria. NICS zz (z) (the out-of-plane component of the chemical shi tensor calculated at z distance above the molecular plane) of PrB 2 À and two reference molecules (the singly p aromatic C 3 H 3 + and the doubly s + p aromatic B 3 À ) are compared in Table S8.…”
Section: B-b 2ps Mo and The Vertical (P T ) And Horizontal (P K ) B-b...mentioning
confidence: 99%
“…Albeit being widely used, the NICS values may be articially lowered by the local paramagnetic current around the Pr nucleus in PrB 2 À , thus may give negative values even if a global ring-current is non-existent and fail to assess aromaticity in some metallic systems. [96][97][98][99][100] However, the NICS values can still help to provide helpful information about aromaticity when combining with other criteria. NICS zz (z) (the out-of-plane component of the chemical shi tensor calculated at z distance above the molecular plane) of PrB 2 À and two reference molecules (the singly p aromatic C 3 H 3 + and the doubly s + p aromatic B 3 À ) are compared in Table S8.…”
Section: B-b 2ps Mo and The Vertical (P T ) And Horizontal (P K ) B-b...mentioning
confidence: 99%
“…Recently, the magnetic response of the core electrons was computed, showing the core–electron contributions are localized principally around the nuclei. 38 Nevertheless, for a system containing transition metals or heavy atoms, the core electrons introduce a significant contribution to the total magnetic response 32 as well as the main contribution to the diamagnetic term of the shielding tensor, as previously reported. 39 It will be evident in the magnetically induced ring currents (MICD) and the inclusion of diatropic responses close to the atomic cores.…”
Section: Introductionmentioning
confidence: 54%
“…We recently showed that the magnetic response of the π electrons of C 60 has an antiaromatic character to the strong paratropic current density on the inside, 11 which promotes a deshielding cone, 11,12 whereas recent calculations point out that internal cage shielding seems to be caused by σ delocalization. 13…”
Section: Introductionmentioning
confidence: 99%
“…We recently showed that the magnetic response of the p electrons of C 60 has an antiaromatic character to the strong paratropic current density on the inside, 11 which promotes a deshielding cone, 11,12 whereas recent calculations point out that internal cage shielding seems to be caused by s delocalization. 13 Multilayer fullerenes, also known as carbon nano-onions (CNOs), are a class of concentric fullerenes with spacing distances between the carbon layers of about 3 to 4 Å. [14][15][16] Since fullerenes have generally the 5-MRs surrounded by 6-MRs.…”
Section: Introductionmentioning
confidence: 99%